4th International Conference on Forensic Sciences, Forensic Medicine and Criminology 2023 (INFOMEC 4.0) - Mohd Yusof, Muhammad Jefri; Abu Bakar, Nurul’Ain; Zainol Abidin, Najihah; Yu, Ke Xin; Kue, Chin Shiang; Abdullah, Noor Faradilla; Sampath Rajan, Sureshkumar (Life Sciences, Medicine and Biomedicine, 2024)
The INFOMEC 2023 organized by the Management and Science University (MSU) is proud to celebrate the 4th anniversary of the International Conference on Forensic Science, Forensic Medicine, and Criminology. This is a premier gathering of experts from around the world who will be sharing their knowledge and expertise, exchange ideas, and discuss the latest advancements and techniques in the field. The conference features a diverse range of topics related to forensic science, forensic medicine, and criminology, including forensic pathology, forensic toxicology, forensic DNA analysis, crime scene investigation, forensic psychology, and criminal profiling, among others. Participants will have the opportunity to attend keynote presentations, poster sessions, and network with colleagues and peers from academia, government, and industry. The conference is an excellent platform for researchers, practitioners, and students to present their research findings and gain valuable feedback from experts in the field. Overall, the International Conference on Forensic Science, Forensic Medicine, and Criminology is an essential event for anyone involved in the fields of forensic science, forensic medicine, and criminology, providing an opportunity to stay up-to-date with the latest trends and developments, and contribute to the advancement of the field.